Epigenetic modification of mesenchymal stromal cells derived from bone marrow and embryonal tumors to facilitate immunotherapeutic approaches in pediatric malignancies - Kruchen, Anne; Johann, Pascal-David; Rekowski, Laura; Müller, Ingo (Current issues in molecular biology, 2023)
Mesenchymal stromal cells (MSC) are part of the bone marrow architecture and contribute to the homeostasis of hematopoietic stem cells. Moreover, they are known to regulate immune effector cells. These properties of MSC are pivotal under physiologic conditions, and they may aberrantly also protect malignant cells. MSCs are also found in the leukemic stem cell niche of the bone marrow and as part of the tumor microenvironment. Here, they protect malignant cells from chemotherapeutic drugs and from immune effector cells in immunotherapeutic approaches. Modulation of these mechanisms may improve the efficacy of therapeutic regimens. We investigated the effect of the histone deacetylase inhibitor (HDACi) suberoylanilide hydroxamic acid (SAHA, Vorinostat™) on the immunomodulatory effect and cytokine profile of MSC derived from bone marrow and pediatric tumors. The immune phenotype of MSC was not markedly affected. SAHA-treated MSC showed reduced immunomodulatory effects on T cell proliferation and NK cell cytotoxicity. This effect was accompanied by an altered cytokine profile of MSC. While untreated MSC inhibited the production of certain pro-inflammatory cytokines, SAHA treatment led to a partial increase in IFNγ and TNFα secretion. These alterations of the immunosuppressive milieu might be beneficial for immunotherapeutic approaches.